Prospek Keefektifan Implementasi Peraturan Tentang Peningkatan Intensitas Bangunan di Wilayah DKI Jakarta: Suatu Aspek Manajemen Pembangunan Fisik Kota Tinjauan Pengalaman di DKI Jakarta - Abimanyu, Udin (Center for Research and Community Services ITB, 1996)
Jakarta is experiencing rapid economic and population growth. This growth requires the ability of the city to cope. One of the demands of this growth is the ever increasing need of space in a situation where the supply of land is becoming more limited. One way to solve this problem is by intensifying the use of land especially in areas with strategic social and economis value. The objective of this intensification program is to increase the intensity of city ‘s space. This intensification program is supported by Governor of DKI Jakarta Decree No. 678/1994 on Building Intensification in DKI Jakarta Area. This decree also acts as guidance and control of development and to make the spatial plan more effective . The effectiveness of the implementation of this decree is highly depended on the consistency of the urban management in implementing various development regulations such as RUTR, RBWK, RTR, and RUK.